Architecting technology transitions: A sustainability‐oriented sociotechnical approach. Issue 2 (23rd October 2012) - Davis, Kim; Mazzuchi, Thomas; Sarkani, Shahram
Abstract Achieving sustainability involves complex processes of technology, people, institutions, and the environment. The sustainability challenge requires a combination of social, political, and technological efforts. This paper discusses processes for technological change in order to meet the sustainability challenge. These complex processes are found to be a suitable application for systems engineering and for systems architecture in particular. Based on a thorough review of the literature, an architecture framework is developed to support management of portfolios of sustainable technology projects. This architecture framework is validated through a case study process, providing enhancements and lessons learned. The full architecture framework construct and associated proposed implementation approaches are presented, demonstrating the need for and applicability of such systems engineering approaches to achieve sustainability. Lessons learned from case studies and development of representative architectures are also described. ©2012 Wiley Periodicals, Inc. Syst Eng 16